Electrophysiological Correlates of Emotional Content and Volume Level in Spoken Word Processing - Grass, Annika; Bayer, Mareike; Schacht, Annekathrin (Frontiers in Human Neuroscience, 2016)
For visual stimuli of emotional content as pictures and written words, stimulus size has been shown to increase emotion effects in the early posterior negativity (EPN), a component of event-related potentials (ERPs) indexing attention allocation during visual sensory encoding. In the present study, we addressed the question whether this enhanced relevance of larger (visual) stimuli might generalize to the auditory domain and whether auditory emotion effects are modulated by volume. Therefore, subjects were listening to spoken words with emotional or neutral content, played at two different volume levels, while ERPs were recorded. Negative emotional content led to an increased frontal positivity and parieto-occipital negativity – a scalp distribution similar to the EPN – between ~ 370 and 530 ms. Importantly, this emotion-related ERP component was not modulated by differences in volume level, which impacted early auditory processing, as reflected in increased amplitudes of the N1 (80 130 ms) and P2 (130 265 ms) components as hypothesized. However, contrary to effects of stimulus size in the visual domain, volume level did not influence later ERP components. These findings indicate modality-specific and functionally independent processing triggered by emotional content of spoken words and volume level.